Interleukin-22 promotes cell proliferation to combat virus infection in human intestinal epithelial cells - Guo, Cuncai; Sharma, Ashwini Kumar; Guzmán, José; Herrmann, Carl; Boulant, Steeve; Stanifer, Megan (Journal of interferon & cytokine research, 2024)
Interferon lambdas (IFN-λs) are crucial to control virus infections at mucosal surfaces. Interleukin-22 (IL-22) was reported to help IFN-λ control rotavirus infection in the intestinal epithelium of mice either by aiding in the induction of interferon-stimulated genes (ISGs) or by increasing cell proliferation thereby clearing virally infected cells. We investigated whether IL-22 and IFN-λs exhibit similar synergistic effects in human intestinal epithelial cells (IECs) models. Our results showed that co-treatment of IL-22 and IFN-λ induced more phosphorylation of STAT1 than either cytokine used alone. However, this increased STAT1 activation did not translate to increased ISGs production or antiviral protection. Transcriptomics analysis revealed that despite sharing a common subunit (IL-10Rb) within their heterodimeric receptors and activating similar STATs, the signaling generated by IL-22 and IFN-λs is independent, with IFN-λ signaling inducing ISGs and IL-22 signaling inducing cell proliferation genes. Using human intestinal organoids, we confirmed that IL-22 increased the size of the organoids through increased cell proliferation and expression of the stem cell marker (OLFM4). These findings suggest that in human intestinal cells, IFN-λs and IL-22 act independently to clear virus infections. IFN-λs induce ISGs to control virus replication and spread, whereas IL-22 increases cell proliferation to eliminate infected cells and repair the damage epithelium. Although these two cytokines do not act synergistically, each plays a key function in the protection of human IECs.
Online veröffentlicht: 10. Oktober 2024
Gesehen am 28.04.2025